The Relationship between Assertive Skills and Career Maturity in High School Students - Abdul Hadi; Edi Purwanta; Budi Astuti; Arini Febriana (Journal of Education Research, 2026)
This study aims to determine the relationship between assertiveness skills and career maturity of high school students. This research method uses a quantitative approach with a correlational research type. The research subjects were students in grades X and XI in a high school environment. Sampling was carried out using a simple random sampling technique with a sample size of 258 students. The research instruments used were assertiveness skills scales and career maturity scales that have been tested for validity and reliability. Data analysis used simple linear regression analysis with the help of the SPSS Version 25 program. The results of the simple regression analysis showed a calculated t value > t table, namely 21.421 > 1.969 and a significance value of 0.000 < 0.05, which means there is a positive and significant relationship between assertiveness skills and career maturity. High assertiveness skills have been shown to have a positive impact on students' career maturity levels. This study provides implications that guidance and counseling interventions that focus on increasing assertiveness can help students make more mature career decisions that are in accordance with their potential and interests.